Revitalization of Sumatra batik motifs from tradition to innovation - Pandanwangi, Ariesa; Ratnadewi, Ratnadewi; Prijono, Agus (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2025)
Sumatran batik has motifs that have deep meanings adopted from everyday life, and many are already rarely produced.The problem in this study is how the process of revitalizing Sumatran batik will be downstream into the creative industry. The purpose of this study is to create a digital revitalization model for rare Sumatran batik motifs, with a focus on their integration into the local creative industry, which can increase cultural awareness and increase market potential in the creative industry. The method used is descriptive qualitative with a visual language approach. The sample in this study is a digital batik with a sample of the Tarok-tarok Boraspati produced by MSMEs. Results show that digitizing batik motifs not only maintains visual authenticity but also enables scalable and market-relevant innovation, contributing to cultural preservation and creative economic growth. The main result is a structured batik composition that maintains the identity of the main motif while enabling wider commercial applications. This approach offers a replicable model for other cultural regions that aim to combine heritage with innovation and increase global cultural visibility through the creative industry.